Natural Extracts That Stimulate Adipocyte Browning and Their Underlying Mechanisms - Min-Kyeong Lee; Bonggi Lee; Choon Young Kim (MDPI AG, 2021)
Despite progress in understanding the developmental lineage and transcriptional factors regulating brown and beige adipocytes, the role of environmental modifiers, such as food components and natural extracts, remains to be elucidated. Furthermore, the undesirable pleiotropic effects produced by synthetic drugs targeting adipose tissue browning and thermogenesis necessitate research into alternative natural sources to combat obesity and related metabolic disorders. The current review, therefore, focused on the effects of various extracts from foods, plants, and marine products on adipose tissue browning and obesity. In particular, the recent findings of food components and marine products on adipose tissue browning will be discussed here.